Coastal Rural Development Planning: Fishery Food Management - Rudianto Rudianto; Uun Yanuhar (Wacana Journal of Social and Humanity Studies, 2018)
The planning of coastal villages based on fishery food management is intended as an approach to strengthen coastal communities to alleviate rural poverty. The pressure on the coast from both anthropogenic processes causes the declining of fishery food supplies. The purpose of this study is to assess the relationship among variables affected fishery food in coastal villages, and to choose the priority to solve degradation of fishery food supplies. Case studies were selected at Tamban beach, Malang Regency. The research method used Partial Least Square (PLS) and Analytical Hierarchy Process (AHP) approach. The results show that the coastal rural development planning based on fishery food management is strongly depending on the relationship among the agricultural environment, alleviating rural poverty and fishery food management. The priorty parameter forÂ  the agricultural Â environment is that the role of private sector and handling skyrocketing food prices. whereas, the priority solution for rural poverty is that supply access on education and health as well as supplying growth opportunity for job creation. Furthermore, the priority for fishery food management is to increase capacity of local people capacity to prepare management plan and the second priority is that the government provide policy and regulatory framework.